MPCs in an economic crisis: Spending, saving and private transfers - Thomas F. Crossley; Paul Fisher; Peter Levell; Hamish Low (Institute for Fiscal Studies (IFS), 2021)
MPCs were directly elicited from a representative sample of UK adults in July 2020 using receipt of a hypothetical unanticipated, one-time income payment. Reported MPCs are modest, around 11% on average. They are higher, but still modest, for individuals in households with high current needs. These low MPCs may be a consequence of the prevailing economic uncertainty. Significant fractions of respondents report they would use a windfall to pay down debt, or that they would change their transfer payments to or from family and friends. The latter means that the aggregate MPC out of a stimulus payment need not equal the population-average MPC.
Keywords: D12; D14; E21; 330; spending; MPC; crowding out; COVID-19